2017
DOI: 10.1017/s1041610217000758
|View full text |Cite
|
Sign up to set email alerts
|

EEG beta 2 power as surrogate marker for memory impairment: a pilot study

Abstract: EEG beta 2 power recorded during a backward counting condition with eyes closed can be used as surrogate marker for verbal memory impairment in geriatric patients. Antidepressant treatment was correlated with EEG data in resting state but not in counting condition. Further studies are necessary to verify the results of this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Low cost spontaneous speech data had been used by researchers to detect MCI or AD [14]- [17]. Relatively low-cost electroencephalography (EEG) is also being investigated to detect [2], [7], [18]- [23] and classify [21] MCI from other diseases that affect the cognitive state. Multi-channel EEG data have been used to characterize MCI or AD using EEG signals in various literature such as: (i) mismatch negativity (MMN) and auditory P300 component from 256-channel EEG [2], (ii) features extracted by recurrence quantification analysis (RQA) and cross recurrence quantification analysis (CRQA) from 14-channel EEG [21], (iii) spectral features extracted from 19-channel EEG [7], (iv) auditory P2 component computed from 64-channel EEG [22], (v) the auditory mismatch negativity (MMN) from 19-channel EEG [23], (vi) event-related potential (ERP) amplitude and latency from 256-channel EEG [24], (vii) accuracy and response time during low and high working memory conditions of memory task using 32channel EEG [19] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Low cost spontaneous speech data had been used by researchers to detect MCI or AD [14]- [17]. Relatively low-cost electroencephalography (EEG) is also being investigated to detect [2], [7], [18]- [23] and classify [21] MCI from other diseases that affect the cognitive state. Multi-channel EEG data have been used to characterize MCI or AD using EEG signals in various literature such as: (i) mismatch negativity (MMN) and auditory P300 component from 256-channel EEG [2], (ii) features extracted by recurrence quantification analysis (RQA) and cross recurrence quantification analysis (CRQA) from 14-channel EEG [21], (iii) spectral features extracted from 19-channel EEG [7], (iv) auditory P2 component computed from 64-channel EEG [22], (v) the auditory mismatch negativity (MMN) from 19-channel EEG [23], (vi) event-related potential (ERP) amplitude and latency from 256-channel EEG [24], (vii) accuracy and response time during low and high working memory conditions of memory task using 32channel EEG [19] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kaiser et al identified significant positive correlations between frontal and parietal beta powers and delayed memory recall ( 95 ). Additionally, through time-frequency analysis, Axmacher et al found that reduced slow hippocampal activity in the delta frequency range supported long-term memory formation ( 96 ).…”
Section: Discussionmentioning
confidence: 90%
“…Jiang et al demonstrated that successful long-term memory encoding corresponds to decreased alpha power in the sensory region of the attended target and increased power in the region of the ignored target, thereby suppressing distractions during the rehearsal period (94). Similarly, Kaiser et al identified significant positive correlations between frontal and parietal beta powers and delayed memory recall (95). Additionally, through time-frequency analysis, Axmacher et al found that reduced slow hippocampal activity in the delta frequency range supported long-term memory formation (96).…”
Section: Higher Delayed Recall and Diminished Sw In Ad Under Eo In De...mentioning
confidence: 99%
“…The comparable beta power in the frontal region between conditions demonstrated that learners had involved similar cognitive resources in vocabulary encoding and comprehension, whether with generated or provided contextual clues. However, higher parietal beta power was associated with internal-generated contextual clues since learners' recall processes typically involve retrieving contextual clues from their prior knowledge, alongside cognitive involvement during semantic processing (Tschentscher and Hauk, 2016;Kaiser et al, 2017). Besides the expected regions, greater beta power was also observed in the fronto-central, occipital, and temporoparietal regions when learners generated contexts themselves.…”
Section: The Impact Of Contextual Clues On Efl Learners' Mental Effor...mentioning
confidence: 89%